Content Analysis of the Topics of Ageing-related Theses at the University of Social Welfare and Rehabilitation Sciences in Iran - Robab Sahaf; Hamid Reza Khankeh; Yadollah Abolfathi Momtaz; Arya Hamedanchi (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives "Ageing" has created challenges for societies, particularly in developing countries. In this regard, the "Research Agenda on Ageing for the 21st century" (RAA-21) has been prepared and published through a joint project of the "United Nations Program on Ageing" and the "International Association of Gerontology and Geriatrics." The University of Social Welfare and Rehabilitation Sciences is the first university in Iran that has admitted students in Gerontology, and currently has the largest number of students studying the subject of "Ageing." The current study aims to compare the topics of dissertations on ageing in the University with the priorities of RAA-21, because no similar study has been conducted at the University so far. Methods & Materials total of 248 dissertations and proposals on "Ageing" were included in this study. The titles were categorized into three levels (priority, research area, and specific topic) with a deductive content analysis approach using RAA-21 guidelines. The results were qualitatively described and compared with RAA-21 priorities. Results The fourth and fifth priorities of RAA-21 ("healthy ageing" as well as "biology and diseases") were identified as the most common priorities in the dissertations of both the University and the Gerontology Department (39.9% and 21%, respectively). The second priority of RAA-21 ("material security") had the least number of dissertations (3.3%). With respect to "research areas," the highest number of dissertations was conducted in the "physical and mental function"(21.8%) and then "biomedical" and "healthy ageing" (19% each) subcategories. "Macro-societal changes and development" and "poverty" subcategories had the least number of dissertations (0.0% and 0.4%, respectively). Conclusion distribution of dissertation topics conducted on "Ageing" at the University does not match with the priorities of RAA-21. As a descriptive study cannot present a certain causal relationship, an investigation into the reason for the differences is suggested for further studies. Moreover, it is also useful to prepare the national priorities for research on "Ageing," using need assessment and RAA-21 as guidelines.